No Association between FCγR3B Copy Number Variation and Susceptibility to Biopsy-Proven Giant Cell Arteritis. (20th August 2013) - Dunstan, Emma; Lester, Sue; Black, Rachel; Rischmueller, Maureen; Chan, Helen; Hewitt, Alex W.; Hill, Catherine L.
Abstract : Objective . To determine the relationship between FCGR3B gene copy number variation (CNV) and biopsy proven giant cell arteritis (GCA). Methods . FCGR3B CNV was determined in 139 Australian biopsy proven GCA patients and 162 population matched controls, using a duplex qPCR assay and RNase P as the reference gene. Copy number was determined using Copy Caller software (v.1.0, Applied Biosystems, USA). CNV genotypes were classified into 3 groups (<2, 2, 3+) for analysis purposes, and analysis was performed using logistic regression. Results . All GCA patients had a positive temporal artery biopsy, and the most common presenting symptoms were visual disturbance and temporal headache. The mean age of patients at biopsy was 74 years (range 51–94) and 88/139 (63%) were female. The frequency of low (<2) FCGR3B copy number was comparable between GCA patients (9/139 = 6.5 %) and controls (10/162 = 6.2 %), as was the frequency of high (3+) FCGR3B copy number (15/130 (10.8%) in GCA patients versus 13/162 (8.0%) in controls). Overall there was no evidence that FCGR3B CNV frequencies differed between GCA patients and controls (χ 2 = 0.75, d f = 2, P = 0.69 ). Conclusion . FCGR3B CNV is not associated with GCA; however, replicate studies are required.